2012
DOI: 10.5539/ass.v8n2p119
|View full text |Cite
|
Sign up to set email alerts
|

EFL Students’ Attitudes towards Learning English Language: The Case of Libyan Secondary School Students

Abstract: This study investigated Libyan secondary school students' attitudes towards learning English in terms of the behavioral, cognitive and emotional aspects. It also explored whether there is any significant difference in the students' attitudes towards English language based on their demographic profiles i.e., gender, field and year of study. A total of 180 participants in the three study years from three specializations of Basic Sciences, Life Sciences, and Social Sciences took a questionnaire as a measuring ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 10 publications
10
93
7
Order By: Relevance
“…Abidin [6] found that students who were educated by using Problem-Based learning achieved the learning goal successfully. In line with that, a research done by Othman & Shah [7] also found a similar result that this particular learning model had a significant impact to the students' learning result.…”
Section: Introductionmentioning
confidence: 99%
“…Abidin [6] found that students who were educated by using Problem-Based learning achieved the learning goal successfully. In line with that, a research done by Othman & Shah [7] also found a similar result that this particular learning model had a significant impact to the students' learning result.…”
Section: Introductionmentioning
confidence: 99%
“…analysis. The questionnaire used for this research was compiled according to the questionnaires used for the purpose of examining attitudes towards a foreign language (Mihaljević Djigunović, 1998;Boonrangsri et al, 2004;Zainol et al, 2012;Burgos & Perez, 2015). Dörnyei and Taguchi (2010) stated that questionnaires are one of the most frequent and reliable methods for collection data in L2 research, because several types of information can be thus collected; factual information, and information about attitudes and behaviours.…”
Section: Methodsmentioning
confidence: 99%
“…Sauvignon (1976: 295) expresses the view that attitude is the single most important factor in language learning. Learners' attitude towards language learning is regarded by Zainol Abidin, et al (2012) as one of the main reasons which gravitate learners to study a language. Likewise, Karahan (2007: 84) contends that positive language attitudes draw learners to have positive orientation towards learning English.…”
Section: The Importance Of Attitudes In Language Achievementmentioning
confidence: 99%